Allelopathic effect of endemic South American Bothriochloa species (Poaceae: Andropogoneae). Issue 3 (4th May 2019) - Scrivanti, Lidia R.; Anton, Ana M.
ABSTRACT: The essential oil composition of Bothriochloa velutina has been studied. The principal compounds of essential oils of three South American endemics, B. eurylemma, B. meridionalis and B. velutina were isolated. In laboratory bioassays, the principal compounds inhibited the seed germination and root and shoot growth of lettuce ( Lactuca sativa L.), maize ( Zea mays L.), wintergreen paspalum ( Paspalum guenoarum Arechav.) and lovegrass [ Eragrostis curvula (Schard.) Nees] test species. The aqueous extracts from different plant parts of three species of Bothriochloa inhibited the seed germination and root and shoot growth of test species. Aqueous extracts were more inhibitory to shoot and root elongation than to seed germination. Significant inhibition in shoot length at all concentrations indicated the phytotoxic activity of extracts. The toxicity enhanced with increasing aqueous extract concentrations. The compounds isolated can interfere with seed germination and seedling growth of plants. Consequently, the study of these chemical interactions might be useful to develop new classes of environmentally safe herbicides.